1998
DOI: 10.1105/tpc.10.9.1571
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Signaling Pathway Controlling Induced Systemic Resistance in Arabidopsis

Abstract: Plants have the ability to acquire an enhanced level of resistance to pathogen attack after being exposed to specific biotic stimuli. In Arabidopsis, nonpathogenic, root-colonizing Pseudomonas fluorescens bacteria trigger an induced systemic resistance (ISR) response against infection by the bacterial leaf pathogen P. syringae pv tomato. In contrast to classic, pathogen-induced systemic acquired resistance (SAR), this rhizobacteria-mediated ISR response is independent of salicylic acid accumulation and pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
445
4
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,016 publications
(500 citation statements)
references
References 47 publications
14
445
4
11
Order By: Relevance
“…The Arabidopsis jasmonate response mutant jar1 and the ethylene response mutant etr1, which show a normal response to inducers of SAR, are unable to express ISR after root treatment with P. fluorescens WCS417r (Ref. 46), indicating that signal transduction leading to rhizobacteria-mediated ISR requires responsiveness to both jasmonate and ethylene. Although ISR and SAR seem to follow distinct signalling pathways, 55 trends in plant science reviews February 1999, Vol.…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The Arabidopsis jasmonate response mutant jar1 and the ethylene response mutant etr1, which show a normal response to inducers of SAR, are unable to express ISR after root treatment with P. fluorescens WCS417r (Ref. 46), indicating that signal transduction leading to rhizobacteria-mediated ISR requires responsiveness to both jasmonate and ethylene. Although ISR and SAR seem to follow distinct signalling pathways, 55 trends in plant science reviews February 1999, Vol.…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
“…tomato has been investigated by application of methyl jasmonate and the ethylene precursor 1-aminocyclopropane-1-carboxylate (ACC) as inducing agents 46 (Fig. 3), which, like P. fluorescens WCS417r, are effective in inducing resistance against P. syringae pv.…”
Section: Systemic Resistance Induced By Non-pathogenic Rhizobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, induced systemic resistance (ISR), which is triggered by nonpathogenic root-colonizing bacteria, is JA and ethylene dependent [16,17] and is independent of SA and PR-gene activation [18,19]. The JA response mutant jar1 and the ethylene response mutant etr1 lose ISR upon treatment with Pseudomonas fluorescens WCS417r, but remain normal level of pathogen-induced SAR [20,21], indicating that JA and ethylene responses are critical for the ISR-signaling pathway [22,23]. Analysis of signaling molecules involved in rhizobacteria-madiated ISR suggests that ISR might be associated with another pathogen-induced jasmonate and ethylene defense response, in which a subset of PR genes, such as PR3, PR4, and PR12, were co-regulated by jasmonate and ethylene [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the jasmonic acid (JA)-response mutant jar1-1, a range of ethylene (ET)-response mutants, and the SAR-compromised mutant npr1-1 revealed that components of the JA-and the ET-response are required for triggering WCS417r-mediated ISR, but that like SAR, this induced resistance response depends on NPR1 (Knoester et al, 1999;Pieterse et al, 1998). However, downstream of NPR1, the ISR and the SAR signaling pathways diverge, because unlike SAR, ISR is not accompanied by the concomitant activation of PR genes (Pieterse et al, 1996;Van Wees et al, 1999;Van Wees et al, 1997).…”
Section: Introductionmentioning
confidence: 99%